Modulatory Impact of Oxidative Stress on Action Potentials in Pathophysiological States: A Comprehensive Review - Chitaranjan Mahapatra; Ravindra Thakkar; Ravinder Kumar (MDPI AG, 2024)
Oxidative stress, characterized by an imbalance between the production of reactive oxygen species (ROS) and the body's antioxidant defenses, significantly affects cellular function and viability. It plays a pivotal role in modulating membrane potentials, particularly action potentials (APs), essential for properly functioning excitable cells such as neurons, smooth muscles, pancreatic beta cells, and myocytes. The interaction between oxidative stress and AP dynamics is crucial for understanding the pathophysiology of various conditions, including neurodegenerative diseases, cardiac arrhythmias, and ischemia-reperfusion injuries. This review explores how oxidative stress influences APs, focusing on alterations in ion channel biophysics, gap junction, calcium dynamics, mitochondria, and Interstitial Cells of Cajal functions. By integrating current research, we aim to elucidate how oxidative stress contributes to disease progression and discuss potential therapeutic interventions targeting this interaction.